NK Cell Functional Impairment after Allogeneic Hematopoietic Stem Cell Transplantation Is Associated with Reduced Levels of T-bet and Eomesodermin - Simonetta, Federico; Pradier, Amandine; Bosshard, Carine; Masouridi-Levrat, Stavroula; Chalandon, Yves; Roosnek, Eddy (The Journal of immunology (1950), 2015)
NK cells play a major role in protection against tumor recurrence and infection after allogeneic hematopoietic stem cell transplantation (HSCT). It has been shown that NK cell function after HSCT is impaired, but underlying molecular mechanisms are not well-known. In this report we show that the level of T-bet and Eomesodermin (Eomes), two T-box transcription factors regulating lymphocyte effector functions, is strongly reduced in NK cells from HSCT recipients compared with healthy control subjects. Reduction of T-bet and Eomes expression appeared early and persisted for years after HSCT, affecting all peripheral blood NK cells independently of their differentiation status. Reduced T-bet levels in NK cells from allogeneic HSCT recipients significantly correlated with reduced perforin expression. Acute, but not chronic, graft-versus-host disease, as well as CMV reactivation, was associated with further downregulation of T-bet expression in NK cells. Lower levels of T-bet expression in NK cells were associated with less favorable outcome after HSCT as a result of increased nonrelapse mortality. Collectively, our results provide a possible molecular explanation for the previously reported functional exhaustion of NK cells after allogeneic HSCT and suggest an impact of the NK transcriptional machinery status on HSCT outcome.